2021
DOI: 10.1002/jpen.2271
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of electromagnetic sensing aided post pyloric feeding tube placement (CORTRAK) in patients with thrombocytopenia with or without anticoagulation on the intensive care unit

Abstract: Background The successful initiation of enteral nutrition is frequently hampered by various complications occurring in patients treated in the intensive care unit (ICU). Successful placement of a nasojejunal tube by CORTRAK enteral access system (CEAS) has been reported to be a simple bedside tool for placing the postpyloric (PP) feeding tube. Methods We evaluated the efficacy and side effects using CEAS to establish EN in patients with critical illness, thrombocytopenia, and/or anticoagulation. Results Fifty‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Air insufflation has also been used to flatten the gastric folds. Using IV prokinetics (to increase peristalsis), supine patient's position (removes gastric folding), and massaging the right upper quadrant in an inward and upward direction (to move the tube tip over the duodenal flexure) have also been described to help placement of NJ tube Gerritsen et al 36 Stecher et al 37 DeLegge 19 Electromagnetic (EM)-guided placement of NJ tubes has been found to be a simple, safe, and less costly alternative to radiologic and endoscopic techniques. Additionally, no fasting is required before the procedure.…”
Section: Cardona and Mehta 34mentioning
confidence: 99%
See 2 more Smart Citations
“…Air insufflation has also been used to flatten the gastric folds. Using IV prokinetics (to increase peristalsis), supine patient's position (removes gastric folding), and massaging the right upper quadrant in an inward and upward direction (to move the tube tip over the duodenal flexure) have also been described to help placement of NJ tube Gerritsen et al 36 Stecher et al 37 DeLegge 19 Electromagnetic (EM)-guided placement of NJ tubes has been found to be a simple, safe, and less costly alternative to radiologic and endoscopic techniques. Additionally, no fasting is required before the procedure.…”
Section: Cardona and Mehta 34mentioning
confidence: 99%
“…36 EM-guided placement of NJ tube is feasible and safe in patients with thrombocytopenia. 37 Even though this technique was approved by the U.S. Food and Drug Administration for confirmation of appropriate position of the NJ tube, it was associated with severe complications and even death due to clinicians' failure to recognize lung placement 19…”
Section: Nasoenteric Tubes (Ng and Nj)mentioning
confidence: 99%
See 1 more Smart Citation